Neoadjuvant chemotherapy in advanced epithelial ovarian cancer by histology: A SEER based survival analysis. Issue 4 (27th January 2023) - Liu, Yuexi; Ni, Meng; Huang, Fanfan; Gu, Qiuying; Xiao, Yao; Du, Xinyue
Abstract : To evaluate the prognostic effect of neoadjuvant chemotherapy (NACT) in advanced epithelial ovarian cancer (EOC) patients with different histological subtype. Stage III/IV EOC patients diagnosed between 2010 and 2018 were identified from the surveillance, epidemiology, and end results database (SEER) database and stratified by histological subtype. Kaplan–Meier analysis was used for the assessment of overall survival (OS) cause-specific survival (CSS) before and after matching for baseline characteristics between NACT and primary debulking surgery (PDS) groups. Cox proportional risk model was conducted to identify independent prognostic factors. A total of 13, 582 patients were included in the analysis. Of them, 9505 (74.50%) received PDS and 3253 (25.50%) received NACT. Overall, an inferior OS and CSS was observed among patients with high-grade serous carcinoma (HGSC) receiving NACT, while NACT served as a protective factor in clear cell carcinoma and carcinosarcoma in both original cohorts and adjusted cohorts. For other histo-subtypes, PDS showed survival benefit over NACT in certain cohorts of models. Prognostic effect of NACT in advanced EOC differed from pathological subtypes. Although it served as a risk factor for HGSC, patients with less common subtypes may benefit from NACT.